Three New Indole Diketopiperazine Alkaloids from Aspergillus ochraceus. Issue 4 (17th April 2018) - Wen, Huiling; Liu, Xiaorui; Zhang, Qing; Deng, Yanfang; Zang, Yi; Wang, Jianping; Liu, Junjun; Zhou, Qun; Hu, Linzhen; Zhu, Hucheng; Chen, Chunmei; Zhang, Yonghui
Abstract : Asperochramides A – D (1  – 4 ), a new natural product and three new indole diketopiperazine alkaloids, along with seven known analogs (5  – 11 ), were isolated from the ethyl acetate extract of Aspergillus ochraceus . Their structures were elucidated by extensive spectroscopic analyses, ECD calculation, and single‐crystal X‐ray diffraction analysis. Compounds3 and4 represent a rare group of indole diketopiperazine alkaloid with a 3‐hydroxyl‐2‐indolone moiety. The in vitro anti‐inflammatory effects of compounds1 and3  – 11 were investigated by using LPS‐stimulated murine macrophage RAW 264.7 cells. Compounds1, 8, 10, and11 showed potential anti‐inflammatory activities. Abstract :